2015
DOI: 10.1017/s1478951515000681
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of caregiver social support is associated with cancer survivors' memories of stem cell transplantation: A linguistic analysis of survivor narratives

Abstract: Our findings provide insights to guide research on the mechanisms through which caregiver support influences patient outcomes after stem cell transplantation. For instance, research suggests that these kinds of effects could have implications for survivors' current self-concept, psychosocial functioning, and meaning-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Some studies have shown that ICs' social support varies in quality or effectiveness [6], but this may be a coping response that helps ease the emotional and practical burden of the cancer disease experience [7]. However, ICs' interventions do differ because they have individual differences in skills, motivation, and ability to overcome the difficult situations associated with cancer care [8], and different authors who have considered caregiving a full-time job that imposes a significant burden of responsibility [2,7,9,10] have investigated the high cost of informal care [11] and the need to involve these caregivers in the healthcare team from the moment of diagnosis [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that ICs' social support varies in quality or effectiveness [6], but this may be a coping response that helps ease the emotional and practical burden of the cancer disease experience [7]. However, ICs' interventions do differ because they have individual differences in skills, motivation, and ability to overcome the difficult situations associated with cancer care [8], and different authors who have considered caregiving a full-time job that imposes a significant burden of responsibility [2,7,9,10] have investigated the high cost of informal care [11] and the need to involve these caregivers in the healthcare team from the moment of diagnosis [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…During the allo-HSCT trajectory, patients need care and support from their family members, especially when returning home after the long hospital stay, and there are indications that the level and quality of caregiver support influences patients' transplant experience (Rini et al, 2015). Being a family caregiver in allo-HSCT often includes providing practical and physical care to the patient, as well as emotional support (Bergkvist et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the SEOLCAS has the ability to not only measure the impact that providing end-of-life care has on Hispanic informal caregivers, but also to differentiate between the type of support that they may need depending on their scores. For example, information gathered from the dimension external contingencies will indicate whether instrumental support may be needed and it can orientate the decisions or interventions that must be taken to offer the instrumental support an individual needs (Rini et al, 2015). Equally, the information gathered from the dimension internal contingencies will indicate whether emotional support may be needed and it can orientate the decisions or interventions that must be taken to provide it (Rini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%